2009
DOI: 10.1007/s11259-009-9334-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bioassay to detect reaginic antibodies from the serum of horses affected with Recurrent Airway Obstruction

Abstract: In horses, Recurrent Airway Obstruction (RAO) is an allergic disease that involves IgE mediated Type I Hypersensitivity responses. The development of this type of allergy involves a series of events that begins with reaginic antibodies, mainly IgE and some IgG subclasses. These reaginic antibodies bind with high affinity, via the Fc portion, to FcepsilonRI receptors on the membrane of mast cells and basophils. Once bound, environmental allergens cross-link the antibodies, which results in mast cell degranulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…Therefore it is always essential to run mouse IgE positive controls alongside the experiment (Figure 1), and to maintain a large frozen stock of secreting cells. Other research work, such as 20 have indicated that equine RAO is not related to IgE mediation, which is why some discrepancy can be seen with other publishers such as Moran et al 31 when using total equine serum to test to Ca 2+ influx from RAO suffering horses using unspecific reaginic antibodies, for which different antibodies would be responsible for the cellular Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore it is always essential to run mouse IgE positive controls alongside the experiment (Figure 1), and to maintain a large frozen stock of secreting cells. Other research work, such as 20 have indicated that equine RAO is not related to IgE mediation, which is why some discrepancy can be seen with other publishers such as Moran et al 31 when using total equine serum to test to Ca 2+ influx from RAO suffering horses using unspecific reaginic antibodies, for which different antibodies would be responsible for the cellular Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 92%
“…Ca 2+ mobilization in RBL-2H3 cells Intracellular Ca 2+ mobilization in RBL-2H3 cells was monitored by change in the fluorescence intensity of fura-2AM-loaded cells as previously described (Morán et al 2010). RBL-2H3 cells were adjusted to a concentration of 10 6 cells/ml in RPMI-1640 medium containing 10% FCS plus antibiotics and incubated for 2 hours at 37°C in the presence of 200 μl of serum obtained from RAO-positive and negative horses.…”
Section: Preparation Of F Rectivirgula Antigensmentioning
confidence: 99%
“…In horses, type I hypersensitivity has been investigated, suggesting that this reaction might be involved in immune-mediated diseases such as summer eczema (Larsen et al 1988;Ungar-Waron et al 1990), urticaria, and head shaking (Mansfield et al 1998), as well as RAO (Halliwell et al 1993;Schmallenbach et al 1998;Eder et al 2000;Eder et al 2001;Curik et al 2003;Künzle et al 2007; Morán et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations